Surrounded by idiots : the four types of human behaviour( or, how to understand those who cannot be understood) - Erikson, Thomas (UK : Penguin, 2019)
You are not alone. After a disastrous meeting with a highly successful entrepreneur, who was genuinely convinced he was surrounded by idiots, communication expert and bestselling author, Thomas Erikson dedicated himself to understanding how people function and why we often struggle to connect with certain types of people. Originally published in Swedish in 2014 as Omgiven Av Idioter, Erikons Surrounded by Idiots is already an international phenomenon, selling over 1.5 million copies worldwide, of which over 750,000 copies have been sold in Sweden alone. It offers a simple, yet ground-breaking method for assessing the personalities of people we communicate with in and out of the office based on four personality types (Red, Blue, Green and Yellow), and provides insights into how we can adjust the way(s) we speak and share information. Erikson will help you understand yourself better, hone communication and social skills, handle conflict with confidence, improve dynamics with your boss and team, and get the best out of the people you deal with and manage. He also shares simple tricks on body language, improving written communication and advice on when to back away or when to push on, and when to speak up or indeed shut up. Packed with aha! and oh no! moments, Surrounded by Idiots will help you understand and influence those around you, even people you currently think are beyond all comprehension. And with a bit of luck you can also be confident that the idiot out there isnt you!
Includes index.